The plant alkaloid chelerythrine binds to chromatin, alters H3K9Ac and modulates global gene expression. Issue 7 (19th May 2017) - Banerjee, Amrita; Sanyal, Sulagna; Dutta, Shreyasi; Chakraborty, Payal; Das, Prajna Paramita; Jana, Kuladip; Vasudevan, Madavan; Das, Chandrima; Dasgupta, Dipak
Abstract : Chelerythrine (CHL), a plant alkaloid, possesses antimicrobial, anti-inflammatory, and antitumor properties. Although CHL influences several key signal transduction pathways, its ability to interact directly with nucleoprotein complex chromatin, in eukaryotic cells has so far not been looked into. Here we have demonstrated its association with hierarchically assembled chromatin components, viz. long chromatin, chromatosome, nucleosome, chromosomal DNA, and histone H3 and the consequent effect on chromatin structure. CHL was found to repress acetylation at H3K9. It is more target-specific in terms of gene expression alteration and less cytotoxic compared to its structural analog sanguinarine.